The Effect Of The Role Of Public Manager On The Satisfaction Of The Kerinci Ethnic Community In The Tourism Sector - Hilfa Relonius; Dasman Lanin (Program Pascasarjana Universitas Negeri Makassar, 2022)
Kerinci is an area where there are still indigenous or native Malay ethnic groups scattered in Kerinci Regency which must be preserved and guarded by the Kerinci Regency Tourism and Culture Office. However, problems are still found, because the role of the local government, especially in the tourism sector in Kerinci Regency, has not been fully able to fulfill the wishes of the community and do more concrete things to give its role both internally and externally to the community. In addition, the social life of the community will experience a decline. So that it causes dissatisfaction and injustice that is felt by the community in preserving the culture that has become the regional identity, especially in Kerinci Regency. This study uses quantitative methods with associative research types whose purpose is to determine the effect of the dependent variable (the role of external managers) and (the role of internal managers) on the independent variable (community equity satisfaction). The population in the study is the entire Kerinci community in 2021, which amounts to 250,259 people. The determination of the sample in this study is all using the Slovin formula with an error rate of 7% and a sample of 204 respondents can be obtained. Sampling Technique Using Professional Random Sampling. The results of the study show that there is a partially significant influence of the External Role of Managers on Community Equity Satisfaction from the R square value of 0.086, which is 8.6%. The Internal Manager's Role on Community Equity Satisfaction from an R square value of 0.069 which is 6.9%. And simultaneously from the two dependent variables on community equity satisfaction, the adjusted R square value of 0.144 is 14.4%.